The Effect of Cyberloafing and Job Satisfaction on Employee Performance Mediated by Organizational Commitment to Local Government Employees of Rejang Lebong Regency - Putra, Okka Adittio; Nugroho, Sigit; Praningrum (UNIB Press, 2024)
Abstract : This study aims to analyze the effect of cyberloafing (X1) and job satisfaction (X2) on peformance (Y) mediated by organizational commitment (M). The population in this study were Local Government Employees in Rejang Lebong district. The sample was taken using random sampling. The number of data is 305 respondents who were taken through a google form questionnaire using the partial least squares (PLS) data analysis method. Based on statistical tests, the results showed that cyberloafing had a not significant and negative on peformance and organizational commitment. While job satisfaction has a significant positive effect on peformance as well as organizational commitment which has a significant positive effect on peformance. organizational commitment no mediates cyberloafing on performance, while job satisfaction on performance partially mediates because it is positive and significant. Keywords: Cyberloafing, Job Satisfaction, Organizational Commitment, and Performance Abstrak : Penelitian ini bertujuan untuk menganalisis pengaruh cyberloafing (X1) dan kepuasan kerja (X2) terhadap kinerja (Y) yang dimediasi oleh komitmen organisasi (M). Populasi dalam penelitian ini adalah Pegawai Pemerintah Daerah di Kabupaten Rejang Lebong. Sampel diambil dengan menggunakan random sampling. Jumlah data 305 responden yang diambil melalui kuesioner google form menggunakan metode analisis data partial least squares (PLS). Berdasarkan uji statistik, diperoleh hasil bahwa cyberloafing berpengaruh tidak signifikan dan negatif terhadap kinerja dan komitmen organisasi. Sedangkan kepuasan kerja berpengaruh positif signifikan terhadap kinerja serta komitmen organisasi berpengaruh positif signifikan terhadap kinerja. komitmen organisasi tidak memediasi cyberloafing terhadap kinerja, sedangkan kepuasan kerja terhadap kinerja secara parsial memediasi karena positif dan signifikan. Kata kunci: Cyberloafing, Kepuasan Kerja, Komitmen Organisasi, dan Kinerja